since y = 6-x, use that to get
3x + 2(6-x) = 8
x = -4
Sure looks like C
Solve the following system of equations:
x + y = 6
3x + 2y = 8
A. (11, –5)
B. (–2, 8)
C. ( –4, 10)
D. (2, 4)
2 answers
Multiply first equation by 3
3 x + 3 y = 18
Now:
3 x + 3 y = 18
-
3 x + 2 y = 8
__________
0 + y = 10
y = 10
Put this value in first equation.
x + y = 6
x + 10 = 6
Subtract 10 to both sides
x = - 4
The solution is:
x = - 4 , y = 10
You can write this solution as ( - 4 , 10 )
Answer C
3 x + 3 y = 18
Now:
3 x + 3 y = 18
-
3 x + 2 y = 8
__________
0 + y = 10
y = 10
Put this value in first equation.
x + y = 6
x + 10 = 6
Subtract 10 to both sides
x = - 4
The solution is:
x = - 4 , y = 10
You can write this solution as ( - 4 , 10 )
Answer C